EFEKTIVITAS KEPEMIMPINAN DIGITAL (DIGITAL LEADERSHIP) DALAM MENINGKATKAN INOVASI TIM SECARA REMOTE: EFEKTIVITAS KEPEMIMPINAN DIGITAL (DIGITAL LEADERSHIP) - Mandala Bakti; Aksan; Rudin (JAMB:Journal of Digital Business and Management, 2026)
In the era of digital transformation, remote work patterns have become the new standard, challenging conventional organizational structures. This study aims to analyze the influence of Digital Leadership on increasing Team Innovation in a remote work environment. Using a quantitative approach, data was collected from 115 respondents working in remote teams across various industry sectors. Data analysis was conducted using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method to test the validity, reliability, and causal relationships between variables. The Outer Model analysis results demonstrated a very strong level of validity and reliability, with an Average Variance Extracted (AVE) value of 0.684 and a Composite Reliability of 0.912. Hypothesis testing using the Inner Model revealed that Digital Leadership has a positive and significant effect on Team Innovation, with a Path Coefficient of 0.764 ($P < 0.001). Furthermore, the R-Square value of 0.584 indicates that Digital Leadership explains 58.4% of the variance in Team Innovation, making it a dominant factor in driving creative productivity. Practically, this finding confirms that the effectiveness of team innovation is highly dependent on the leader's ability to clearly communicate a digital vision, adapt to collaboration tools, and build a culture of output-based trust. Effective digital leadership has been shown to break down bureaucratic barriers and provide teams with the autonomy they need to accelerate the execution of creative ideas. This study concludes that strengthening digital leadership capabilities is a fundamental prerequisite for organizations to create sustainable competitive advantage through an inclusive and adaptive work culture transformation in the digital era.